Tutelas diferenciadas nos processos de família - Zwicker, Alexandre Augusto de Mattos (2007)
This study if it constituted in an analysis of the differentiated jurisdictional guardianships. Thus they are considered you differentiate for not bringing something innovative in its form of applicability. One is not about innovative procedures, more yes of the form that are used these procedures. An appropriate model of jurisdictional guardianship to each new situation will not have to exist in the procedural system that to appear, but the procedural systems will have to be amoldados the reality and necessity of the jurisdicionados ones that they need one ready satisfaction of the State to take care of its yearning. In the study we emphasize the state protection through forms of composition of the litigations. We will briefly see the formation of the family in elapsing of the times. Form of calling of the involved one in the procedural demand. E the differentiated guardianships and its applicability in the family processes as the monitória action and exception of daily pay-executividade